4-H Archery Leader Guide: Basic and Advanced Levels, Ages 8–18 Years - Julia S. Kelly; Matt Benge; Glenn Israel (EDIS, 2023)
The purpose of this guide is to provide a resource for archery leaders that includes reflection, application and evaluation with the activities. Written by Julia S. Kelly, and published by the Florida 4-H Youth Development Program, UF/IFAS Extension, June 2023.